AKULTURASI HINDU BUDDHA DI PURA GOA GIRI PUTRI DESA PEKRAMAN KARANGSARI, KECAMATAN NUSA PENIDA, KABUPATEN KLUNGKUNG 2007-2014 - Winata, I Ketut (Humanis; Volume 13. No.3. Desember 2015, 2016)
The purpose of this research are: 1) To understand the factors that led to the acculturation Hindu Buddhist temple Goa Giri Putri Pekraman Karangsari village, Nusa Penida, Klungkung regency, 2) To describe the form of acculturation Hindu Buddhist belief in temple Goa Giri Putri, Pekraman Karangsari village , Nusa Penida, Klungkung regency, and 3) To understand the implications of acculturation Hindu Buddha for people in rural Pekraman Karangsari, Nusa Penida, Klungkung regency. With the presentation of data analysis using descriptive-qualitative method. The results obtained from this study can be presented. The cause of acculturation Hindu Buddha in temple Goa Giri Putri, is: Hindu religion Buddhist, Hindu worship Buddha, and infrastructure Hindu worship Buddha in the temple of Goa Giri Putri. Acculturation forms of Hindu belief in the Buddhist temple of Goa Giri Putri, is: acculturation Hindu Buddha in the history of temple Goa Giri Putri, acculturation Hindu-Buddhist shrines in the temple structure Goa Giri Putri, acculturation Hindu and Buddhist in pengemong and pemedek temple Goa Giri Putri, and acculturation Hindu Buddha in a temple ceremony and upakara in Goa Giri Putri. Hindu Buddhist acculturation implications for rural communities Pekraman Karangsari: social implications, economic implications, religious implications, magical implications, and implications of treatment (usada).
Keywords: Acculturation, Hindu and Buddhist beliefs, Goa Giri Putri Temple